¡Qué divertido es leer! Material de enseñanza para fortalecer la competencia de comprensión lectora en estudiantes de grado 5° (2022)
This degree project shows the need and importance of improving the levels of reading comprehension and reflection in students from the primary years at school. This project stems from my pedagogical practices at the Liceo Femenino Mercedes Nariño, in which the girls prepare themselves in the first half of the year to present the saber 5th tests, during these practices the need arose to create a teaching material that not only to train the girls for these tests but also to strengthen certain skills that the girls need to continue with their school years, since shortcomings were evident in the reading processes carried out by the girls, reading processes that do not allow the girls show good results in the tests knowing 5th and that in addition to this they do not allow them to enjoy doing different types of reading throughout the school. For this reason, that said, in response to the need mentioned above, this document is presented that first theorizes the importance of reading comprehension and reflection in the school years and secondly shows the material that allows the strengthening of comprehension and reflection. reader, a booklet has been designed, whose purpose is to enhance skills in the reading process.